Effect of bimaxillary orthognathic surgery on dysfunction of the temporomandibular joint: a retrospective study of 500 consecutive cases. Issue 8 (October 2019) - Kretschmer, W.B.; Baciuţ, G.; Baciuţ, M.; Sader, R.
Abstract: We investigated the effect of bimaxillary orthognathic surgery on symptoms in the temporomandibular joint (TMJ) and predictive factors for postoperative dysfunction. A total of 500 patients with different craniofacial deformities who were having bimaxillary orthognathic surgery were assessed for overjet, overbite, maximal mouth opening, maximal protrusion, maximal lateral movement to both sides, and symptoms of TMJ dysfunction (pain on palpation, clicking, or crepitus) before operation and one year postoperatively. The panoramic radiographs taken on the same dates were assessed for reduction in the height of the ramus. Other variables were age, sex, segmentation of the maxilla, and additional genioplasty. Changes in the symptoms of dysfunction were investigated with the McNemar test. Measurements of the maximum mandibular movements taken preoperatively and postoperatively were compared using the paired t test. Multivariate logistic regression was used to assess the influence of the variables on symptoms preoperatively and postoperatively. The effect of occlusal stability (overjet and overbite) on postoperative symptoms in the TMJ was investigated with the unpaired t test. Women and class II patients had significantly more pain on palpation preoperatively, and a significant reduction in pain on palpation and clicking after operation. Predictive factors were preoperative crepitus for postoperative pain, and preoperative clicking for postoperative clicking. Patients with and without symptoms showed no significant differences in overjet and overbite postoperatively. Condylar resorption was found in 29 patients (5.8 %), and only 14 of them had symptoms in the TMJ. In patients with no preoperative symptoms or radiological abnormalities of the condyle, condylar resorption was rare (0.8 %). Orthognathic surgery has a beneficial effect on dysfunction of the TMJ as it reduces pain and clicking considerably. Patients should be informed, however, that TMJ disorders could still develop even if they had no symptoms preoperatively.